Information Technology Governance Analysis Of Stmik Palcomtech In The New Normal Era Using Cobit 2019 Method - Ajismanto, Fahmi; Surahmat, Surahmat (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
The pandemic conditions experienced by the world today inevitably force us to practice social distance so that gatherings involving large numbers of people must be avoided first. In universities, especially in the city of Palembang, the use of information technology and learning media is mandatory due to the decision of the minister of education which requires universities to carry out online learning activities. So that information technology governance during a pandemic also has a major influence in the implementation of teaching and learning activities in universities to ensure the quality of the learning and teaching process carried out so that it must be known the shortcomings and advantages of governance which is carried out by conducting further analysis of technology governance in accordance with with the initial goal of education at the university. The method that can be used is to apply the Cobit 2019 where with this method the current maturity level can be known in the application of information technology. The research method in this study uses a descriptive-quantitative method by describing the indicators used as the basis for measurement taken by the Cobit 2019 literature. This study discusses information technology governance form of Design Factor 1 (Enterprise Strategy) to Design Factor 10 (Technology Adoption Strategy) with the result that there are 13 important processes out of 40 total processes in the Cobit 2019 domain that must be considered at STMIK Palcomtech, namely EDM03, APO08, DSS05 EDM02, APO04, APO09, APO12, APO13, BAI01, BAI02, BAI03, BAI06 , MEA03